ICE MAKER COOLING SYSTEM ANALYSIS - Arnolius; Ahmad Eko Suryanto (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2022)
Ice Maker is a tool used to make ice cubes quickly and automatically. For this reason, research was carried out on the ice maker to determine the cooling temperature produced by the ice maker, the purpose of this study was to analyze the cooling time of the ice maker morning, afternoon, and evening. This study uses the True Experimental Design research method, and data collection is 3 times in the morning, afternoon, and evening and the time taken is 10, 20, 25,30,35 minutes, the data taken are compressor work, cooling time, and cooling temperature. The results showed that the maximum temperature is -18°C.